Predictors of positive electrophysiological study in patients with syncope and bundle branch block: PR interval and type of conduction disturbance - Roca‐Luque, Ivo (Clin Cardiol, 2018)
BACKGROUND: Electrophysiological study (EPS) is indicated in patients with syncope and bundle branch block (BBB). Data about predictors of positive EPS in these patients is scarce. OBJECTIVE: To assess clinical and electrocardiographic (ECG) predictors of positive EPS in patients with syncope and BBB. METHODS: Observational single‐center study that included all consecutive patients with syncope and BBB that underwent EPS from January 2011 to June 2017. Results of EPS were considered positive according to current ESC syncope guidelines. RESULTS: During study period, 271 patients were included (64.9% male, age: 73.9 ± 12.2 years, number of syncopal episodes: 2.4 ± 2.5, LVEF: 56.1 ± 9.9%). Type of BBB: RBBB + LAFB/LPFB in 39.8%, isolated LBBB in 38.7% and isolated RBBB in 18.5% of the patients. Duration of QRS and PR interval were 141.9 ± 16.7 and 182.8 ± 52.2 milliseconds. EPS was positive in 41.7% of the patients. In multivariate analysis, conduction disturbance pattern and long PR interval (OR 8.6; 2.9‐25; P < 0.0001) were predictors of positive EPS. Conduction disturbance patterns related with positive EPS were: BBB different than isolated RBBB (OR 15.2; 2.2‐23.4; P = 0.005), LBBB or RBBB+long PR + left fascicular block (OR 4.5; 1.06‐20.01; P < 0.042), and RBBB+left fascicular block compared with LBBB (OR 4.8; 1.2‐16.7; P = 0.025). Clinical factors and syncope characteristics were not related with EPS result. CONCLUSIONS: Diagnostic yield of EPS in patients with syncope and BBB is moderate (41%). Type of conduction disturbance pattern and PR interval are associated with the electrophysiological (EP) test result. Patients with LBBB or bifascicular block have the highest rate of positive EP test. Long PR interval increases the proportion of positive EPS in all conduction disturbance patterns.